2014
DOI: 10.1208/s12248-014-9589-4
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Lipolysis Data Does Not Adequately Predict the In Vivo Performance of Lipid-Based Drug Delivery Systems Containing Fenofibrate

Abstract: The present study investigated the utility of in vitro lipolysis performance indicators drug solubilization and maximum supersaturation ratio (SR(M)) for their predictive use for the in vivo performance in a minipig model. The commercial Lipanthyl formulation and a series of LbDDS based on identical self-nanoemulsifying drug delivery systems (SNEDDS) containing 200 mg of fenofibrate, either dissolved or suspended, were subjected to combined gastric (pH 2) and intestinal (pH 6.5) in vitro lipolysis. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 43 publications
5
86
0
Order By: Relevance
“…In agreement with a previous study, the Hf precipitating during in vitro lipolysis was amorphous. Interestingly, the drug precipitates in the presence of orlistat were also found to be amorphous by X-ray powder diffraction (XRPD) (data not shown) (7). Precipitation in the presence of orlistat can be ascribed to the physical instability of the super-saturated system where the drug precipitates over time because of the energy induced by the stirring.…”
Section: Dynamic In Vitro Lipolysismentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with a previous study, the Hf precipitating during in vitro lipolysis was amorphous. Interestingly, the drug precipitates in the presence of orlistat were also found to be amorphous by X-ray powder diffraction (XRPD) (data not shown) (7). Precipitation in the presence of orlistat can be ascribed to the physical instability of the super-saturated system where the drug precipitates over time because of the energy induced by the stirring.…”
Section: Dynamic In Vitro Lipolysismentioning
confidence: 99%
“…Recent studies in dogs and minipigs have shown that the bioavailability of a drug in super-SNEDDS is equal to or better than that in conventional SNEDDS when the same dose is given. Thus, the number of capsules to be ingested to obtain the desired dose can be decreased (5)(6)(7). However, due to the lower cost and the ease of handling of rats compared to dogs and minipigs, studies in rats are often preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Food effect 31 In vitro in vivo correlations (IVIVC) 32 Poorly water soluble drugs (PWSD) 33 3 4 a b s t r a c t 35 Novel formulations that overcome the solubility limitations of poorly water soluble drugs (PWSD) are 36 becoming ever more critical to a drug development process inundated with these compounds. There is 37 a clear need for developing bio-enabling formulation approaches to improve oral bioavailability for 38 PWSD, but also to establish a range of predictive in vitro and in silico biopharmaceutics based tools for 39 guiding formulation design and forecasting in vivo effects.…”
mentioning
confidence: 99%
“…It is not sufficient to assume that only solubilized drug will be available for absorption, when applying in vitro lipolysis models, as recent studies have shown that precipitated drug depending on its solid state might be available for absorption (39)(40)(41). More studies are, however, needed in order to fully elucidate how drug distribution data from in vitro lipolysis are interpreted as recent studies have found discrepancies between drug distribution data and bioavailability (42,43). For the more hydrophilic LBFs, as IIIA-LC, the un-ionized-ionized ratio does only change slightly, both at physiological (1.4 mM) and nonphysiological (10 mM) calcium levels.…”
Section: Discussionmentioning
confidence: 99%